Unraveling the Nagoya Protocol - Morgera, Elisa (Legal Studies on Access and Benefit-sharing, 2014)
The Nagoya Protocol is an unprecedented international environmental agreement that equally addresses development, distributive justice, and environmental sustainability. With a balanced view of the various possible interpretations of the Protocol provisions, in light of different national and regional perspectives, and a systematic highlighting of its legal innovations, Unraveling the Nagoya Protocol: A Commentary on the Nagoya Protocol on Access and Benefit-sharing to the Convention on Biological Diversity will serve as a seminal work for all those interested in the environment, human rights, economics and both legal and scientific innovations. Readership: Academics and practitioners interested in international environmental law, biodiversity, human rights and sustainable development.